1998
DOI: 10.1088/0953-2048/11/2/012
|View full text |Cite
|
Sign up to set email alerts
|

Bi(Pb)-2223 phase formation in Ag-sheathed tapes: the role of oxygen partial pressure during sintering

Abstract: phase formation has been studied in Ag-sheathed multifilamentary tapes processed in different oxygen partial pressures during sintering. In the furnace the total pressure was always kept at and the volume fraction of was varied. The samples prepared for the series were characterized by the critical current density , ac susceptibility and x-ray diffraction. Detailed investigations of the microstructure were carried out by SEM and TEM for samples sintered at 8 and 10% oxygen. The formation of the Bi(Pb)-2223 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Figure 1 demonstrates that J c is more sensitive to the heat treatment temperature than the 2223 fraction and the texture. Müller et al [18] have reported similar phenomena but their work did not include texture observations. In the low temperature range (<826 • C) the phase purity and texture are the main controlling factors for J c .…”
Section: Current Limiting Factorsmentioning
confidence: 93%
“…Figure 1 demonstrates that J c is more sensitive to the heat treatment temperature than the 2223 fraction and the texture. Müller et al [18] have reported similar phenomena but their work did not include texture observations. In the low temperature range (<826 • C) the phase purity and texture are the main controlling factors for J c .…”
Section: Current Limiting Factorsmentioning
confidence: 93%
“…The effect of the intergrowths on I c has been discussed in the literature but is not yet well understood. 21,22) As it is considered that the presence of Bi-2212 grains in the oxide filaments reduces the current carrying capacity of Bi-2223 wires, Bi-2212 grain reduction is important.…”
Section: Controlled Overpressure Sintering Processmentioning
confidence: 99%
“…An excess of PbO corresponding, in weight, to a percentage of the PbO used firstly was added at the beginning for the third method and at the final calcination step for the other methods. The precursor was made from a mixture of SrCO 3 , CaCO 3 , and CuO in the first method, while in the second method only SrCO 3 and CaCO 3 were used. For the first and the second method respectively, the first calcination was at 920 °C during 48 hours and at 1250 °C during 5 to 10 hours, the second calcination at 835 °C during 144 hours and at 845 °C during 5 to 10 hours, the final calcination at 835 °C during 60 hours and at 845 °C during 60 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Generally the phases were obtained with an excess of Bi and in one case with Ca in excess and Sr deficient. Critical current densities of Bi(Pb)-2223 silver sheathed tapes have been correlated by Müller et al [3] to conditions of preparation in the powder in tube method. Their results show that higher values of the critical current density are obtained with higher partial pressure of oxygen and higher sintering time leading in the same time to higher Bi(Pb)-2223 fraction.…”
Section: Introductionmentioning
confidence: 97%